2009
DOI: 10.1038/nmeth1209-934
|View full text |Cite
|
Sign up to set email alerts
|

Addendum: Literature-curated protein interaction datasets

Abstract: 934 | VOL.6 NO.12 | DECEMBER | nature methods addenda, corrigenda and errataWe assessed literature-curated protein-protein interaction (PPI) datasets for the parameters of completeness, coverage and quality by several means, concluding that such datasets might be "possibly of lower quality than commonly assumed." A Correspondence 71 by members of the International Molecular Exchange Consortium (IMEx), while accepting many of our points, objected to our recuration exercise to assess quality, finding our criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…Indeed, divergent organism assignments, the use of alternative protein identifiers, or different representation of complexes, although not reflecting actual curation errors, may lead to misinformation. These issues were raised in a recent study ( 28 , 30 ), which suggested that ‘errors’ of the type ‘wrong protein’ and ‘wrong organism’, among others, are not uncommon, and that the annotation of complexes as sets of spoke-expanded binary interactions is a potential source of concern. Our analysis has quantified these discrepancies on a global level, uncovering many more cases where pairwise discrepancies are attributable to similar issues (Examples 4–6 in the Supplementary Discussion S3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, divergent organism assignments, the use of alternative protein identifiers, or different representation of complexes, although not reflecting actual curation errors, may lead to misinformation. These issues were raised in a recent study ( 28 , 30 ), which suggested that ‘errors’ of the type ‘wrong protein’ and ‘wrong organism’, among others, are not uncommon, and that the annotation of complexes as sets of spoke-expanded binary interactions is a potential source of concern. Our analysis has quantified these discrepancies on a global level, uncovering many more cases where pairwise discrepancies are attributable to similar issues (Examples 4–6 in the Supplementary Discussion S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…While all these problems are well known to database curators ( 28–30 ), the extent to which the ensuing differences impact the data currently stored across major PPI databases has so far not been quantified. The increasing number of non-experts who rely on PPI data for their research therefore often tend to ignore these problems altogether.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the endemic problems of cross-referencing genes and proteins across biological databases ( 34 ), as well as to other more specific issues related to PPI literature curation and to the accuracy of the curated data itself ( 35–37 ), researchers should have access to key information about the aggregated data. They need to readily verify how each PPI record was consolidated, or which databases contributed to a given record.…”
Section: Introductionmentioning
confidence: 99%
“…For this study, we considered that among LowBP-LC-Unique (interactions from LowBP-LC supported by a single paper, and not found in the HT dataset), 35% were false positives. The initial report has been debated [ 25 , 26 ] and this may be an overestimate, which would result in our underestimating the interactome size. Interactions reported in more than one paper, or also detected by an HT experiment, were considered true positives.…”
Section: Resultsmentioning
confidence: 99%